Exploration of Symbiotic Bacteria in the Digestive Tract of Plutella Xylostella L and Their Ability to Degrade Insecticides with the Active Chlorantraniliprole - Fatimatul Jahro; F. Zhang; Jay Prakash Verma (Frontier Advances in Applied Science and Engineering, 2023)
P. xylostella is a major pest of cabbage. Cabbage as one of the horticultural products with a high level of demand. The study aims to explore and characterize bacteria that are symbiotic in the digestive tract of P. xylostella L. Test the ability to biodegrade insecticides made from active chlorantraniliprole by explored bacteria. The research stages were the exploration of bacteria found in the pest P. xylostella. L, life ability test on media containing chlorantraniliprole insecticide, Hypersensitivity Test on Tobacco, identification of selected bacteria. The results of bacterial exploration from the digestive tract of P. xylostella L. obtained 13 bacterial isolates. At the selection stage, 11 bacterial isolates were able to live on media contaminated with chlorantraniliprole insecticide and the results of hypersensitivity tests on tobacco plants showed that all eleven bacterial isolates were pathogenic. The results of exploration of the digestive tract of Plutella xylostella L. found 11 bacteria derived from the genus Pantoea sp., and Erwinia sp. Based on the results of the biodegradation test in general, the clear zone produced by symbiont bacteria increased from 48 hours to 72 hours of observation in all treatments. Of all the isolates, it is known that there are only 2 isolates, namely isolate F2 and isolate F10, which are stable in producing clear zones at 3 different concentration levels. The largest clear zone is produced by isolate F10. While the smallest clear zone is produced by isolate F2.